Adsorption performance of M-doped (M = Ti and Cr) gallium nitride nanosheets towards SO2 and NO2: a DFT-D calculation. Issue 46 (24th July 2020) - Roohi, Hossein; Ardehjani, Nastaran Askari
Abstract : The influences of transition metals (Cr and Ti) doping on the adsorption behavior of SO2 and NO2 gases on the metal doped Gallium Nitride Nanosheet (GaNNS) were explored at Grimme-corrected PBE/double numerical plus polarization (DNP) level of theory. Abstract : The structure, adsorption characteristics, electronic properties, and charge transfer of SO2 and NO2 molecules on metal-doped gallium nitride nanosheets (M-GaNNS s; M = Ti and Cr) were scrutinized at the Grimme-corrected PBE/double numerical plus polarization (DNP) level of theory. Two types, MGa -GaNNS s and MN -GaNNS s, of doped nanostructures were found. The MGa sites are more stable than the MN sites. The results showed that adsorption of SO2 and NO2 molecules on TiGa, N -GaNNS s is energetically more favorable than the corresponding CrGa, N -GaNNS s. The stability order of complexes is energetically predicted to be as NO2 –TiGa -GaNNS > NO2 –TiN -GaNNS > SO2 –TiGa -GaNNS > NO2 –CrN -GaNNS > SO2 –TiN -GaNNS > NO2 –CrGa -GaNNS > SO2 –CrN -GaNNS > SO2 –CrGa -GaNNS . The electron population analysis shows that charge is transferred from MGa, N -GaNNS s to the adsorbed gases. The TiGa -GaNNS is more sensitive than the other doped nanostructures to NO2 and SO2 gases. It is estimated that the sensitivity of TiGa -GaNNS to NO2 gas is more than to SO2 gas.